DESAIN SISTEM BACK-END PADA WEBSITE PROPERTI - Dahlan Susilo; Pranowo Setiaji (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The Clee Ltd prioritizes comfort, speed and customer satisfaction and has a high commitment and professionalism in providing services at relatively affordable prices. The website can reach a wider range of customers and make it easier for customers to find information about products and choose the best offers provided by the company, as well as being a promotion. Business websites require good back-end system support to help create a website as a behind-the-scenes system that processes databases and servers. Design a property website system that has 2 users, namely User and Admin. User as website visitor and Admin as website manager. Users can only access 2 pages, namely the "Login" and "View" pages. Admins can access the "Login", "Manage Email ", "Manage Phone Number ", "Manage Buying Data", "Manage Selling Data", and "Manage Rental Data" pages. Design a back-end website property system by implementing Flask which is a framework that has simplicity, where this trait facilitates the design of the website system and produces an optimal website properly. The implementation of the Flask Framework on the system can be done using the Flask. The Flask route function is a decorator where the URL will be called by the system. Flash serves to display messages. The use of the Flask Framework makes it easier by users to implement the website. The Flask functions used in this system are “login” and “dashboard”. The server can deliver users to do “Buying”, “Selling”, and “Rental” pages. The user can choose one of these systems to move to the selected view.